Crystal plasticity FEM study of twinning and slip in a Mg single crystal by Erichsen test. (1st September 2018) - Hyun, C.S.; Kim, M.S.; Choi, S.-H.; Shin, K.S.
Abstract: The twinning behavior and deformation mechanisms of a pure magnesium (Mg) single crystal were investigated via Erichsen test at room temperature (RT). In order to establish the unique twinning behaviors according to the position of a deformed specimen, microtexture analyses were performed on two cross-sections of a deformed specimen via the electron backscatter diffraction (EBSD) technique. The EBSD results revealed that thin twin bands with different types of twin variants were developed throughout the deformed specimen. The crystal plasticity finite element method (CPFEM), in relation to both the crystallographic slip and deformation twinning, was used to explain the heterogeneous evolution of the twin bands throughout the deformed specimen during the Erichsen test at RT. CPFEM results such as strain components, relative activity of deformation modes, and accumulated volume fraction of twin variants can effectively explain the experimentally observed heterogeneity of twin bands. Graphical abstract: Image 1